Math Saves the Day!: A Song for Budding Scientists - Blake And Katie Hoena, Kelly Canby, Mark Oblinger
Math is important because we use it every day. As they sing along, students will learn that we use math when we bake cookies, go the grocery store, and play with our friends. Text is paired with music and fun illustrations.